Quiz Games as a model for Information Hiding - Bank, Bernd (2016)
We present a general computation model inspired in the notion of information hiding in software engineering. This model has the form of a game which we call quiz game. It allows in a uniform way to prove exponential lower bounds for several complexity problems.